2010
DOI: 10.1002/dvdy.22481
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐ and development‐dependent expression of the small GTPase Arf6 in mice

Abstract: The small GTPase Arf6 is a member of the Arf (ADP-ribosylation factor) family. Although the function of Arf6 has been heavily studied at the cellular level, its physiological function at the whole animal level is largely unknown. In this study, we examined both the tissue distribution and developmental timing of Arf6 expression in wild type mice to obtain valuable information to speculate on the physiological function of Arf6. Western blot analysis using anti-Arf6 antibody revealed that Arf6 was ubiquitously e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 75 publications
2
15
0
Order By: Relevance
“…We have previously reported that Arf6 mRNA is abundantly expressed in epithelial cells of various mouse tissues23. Consistent with this report, Arf6 mRNA was highly expressed in the dorsal skin epidermis of embryonic day (E)15.5 and postnatal day (P)1 mice, although the expression level was extremely lower in P56 adult mice (Fig.…”
Section: Resultssupporting
confidence: 87%
“…We have previously reported that Arf6 mRNA is abundantly expressed in epithelial cells of various mouse tissues23. Consistent with this report, Arf6 mRNA was highly expressed in the dorsal skin epidermis of embryonic day (E)15.5 and postnatal day (P)1 mice, although the expression level was extremely lower in P56 adult mice (Fig.…”
Section: Resultssupporting
confidence: 87%
“…3126, Cell Signaling), anti-cMet (1:200 dilution; SP260, Santa Cruz). Rabbit polyclonal antibody specific to Arf6 was generated as previously described 52 . Western blotting was carried out as previously reported 59 .…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the importance of Arf6 in tumour angiogenesis, it has been reported that Arf6 activation in cancer cells is required for cancer invasion and metastasis 50 . Recent preclinical studies have suggested that anti-angiogenic therapy may promote cancer invasion and metastasis by inducing hypoxia of cancer cells, suggesting that effective cancer therapeutic approaches should involve both inhibition of tumour angiogenesis and cancer invasion/metastasis 51,52 . The critical roles of Arf6 in both tumour vascularization and cancer cell invasiveness/metastasis provide a new cancer therapeutic opportunity.…”
Section: Nature Communications | Doi: 101038/ncomms8925mentioning
confidence: 99%
“…The brain and liver dissected from mice were minced and homogenized on ice in buffer consisting of 20 mM Tris-HCl, pH 7.5, 1 mM EDTA and protease inhibitor cocktail (Nacalai Tesque), followed by the addition of SDS to make a final concentration of 1%. After sonication on ice and centrifugation at 1,000g for 20 min at 4°C, Arf6 in the supernatant was analysed by western blotting with anti-Arf6 antibody 36 as described previously 26 . Actin was also western blotted with anti-actin antibody (Sigma-Aldrich, MO, USA) as an internal standard.…”
Section: Methodsmentioning
confidence: 99%